Sleep patterns and alertness in an elite Super Rugby team during a game week - Dunican, I. A.; Higgin, C. C.; Murray, K.; Jones, M. J.; Dawson, B.; Caldwell, J. A.; Halson, S. L.; Eastwood, P. R. (Journal of Human Kinetics, 2019)
Sleep is a vital component of preparation, performance and recovery for a Super Rugby game. The purpose of this study was to quantify sleep behaviours and alertness of professional rugby union players during training and a game. Thirty-six rugby union players from a Super Rugby team wore a wrist-activity device (Readiband™) to measure sleep for 3 days before, 3 days after and on the night of an evening game. Players were separated into those selected to play the game (n = 23) and those who were not (n = 13). Alertness was assessed for all training and game times using bio-mathematical modelling. Alertness measures =90% were considered to reflect impaired reaction time. Those selected to play in the game progressively increased sleep duration over the nights prior to the game (by 92 min p = 0.05) by delaying wake time. Players went to bed later after the game (02:20 ± 114 min vs 22:57 ± 60 min; p = 0.001) which resulted in decreased sleep duration on game night compared to pre-game nights (296 ± 179 min vs 459 ± 78 min; p = 0.05). Four players did not achieve any sleep on game night. Sleep duration appeared to be truncated by early morning training sessions (before 08:00) on the second and third mornings after the game. Alertness was >90% for all training and game times for all players. In conclusion, in the days leading into a Super Rugby game, players delay morning time at wake and consequently increase sleep duration with post-game sleep reduced in some.